Minimum Competency Assessment (Akm): An Effort To Photograph Numeracy - Irma Rachmah Hidayah; Tri Atmojo Kusmayadi; Laila Fitriana (Journal of Mathematics and Mathematics Education, 2021)
The National Literacy Movement (GLN) refers to the World Economic Forum (WEF), and the Boston Consulting Group (BCG) states that literacy numeracy is one of the basic literacy that must be mastered in the 21st century. However, PISA results show that Indonesian students have low literacy numeracy skills. The Ministry of Education followed up to replace the National Examination (UN) with a Minimum Competency Assessment (AKM). AKM is an essential competency assessment that is tested on students used to measure learners' reasoning ability when faced with problems that require literacy and numeracy skills, namely problems that require basic mathematical knowledge. This study uses the method of literature study. This study aims to examine efforts to improve numeracy capabilities. Efforts that can be made to improve numeracy skills are by providing materials and integrating learning with ethnomathematics approaches, giving higher-order thinking skills (HOTS) that are associated with real life, and utilization of interactive learning games